The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1155/2015/286589
|View full text |Cite
|
Sign up to set email alerts
|

A Task Allocation Algorithm Based on Score Incentive Mechanism for Wireless Sensor Networks

Abstract: A wireless sensor network (WSN) consists of many resource constraint sensor nodes, which are always deployed in unattended environment. Therefore, the sensor nodes are vulnerable to failure and malicious attacks. The failed nodes have a heavily negative impact on WSNs' real-time services. Therefore, we propose a task allocation algorithm based on score incentive mechanism (TASIM) for WSNs. In TASIM, the score is proposed to reward or punish sensor nodes' task execution in cluster-based WSNs, where cluster head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For example, the mechanism proposed in [19], motivates the agents to exert the effort as desired by the requester/controller and truthfully report their private worker quality and data to the requester. Another task allocation incentive-based mechanism to achieve the network load balance and energy consumption has been proposed for wireless networks in [20]. In this work, a scoring based approach is proposed to reward or punish agents for the given task execution.…”
Section: Related Workmentioning
confidence: 99%
“…For example, the mechanism proposed in [19], motivates the agents to exert the effort as desired by the requester/controller and truthfully report their private worker quality and data to the requester. Another task allocation incentive-based mechanism to achieve the network load balance and energy consumption has been proposed for wireless networks in [20]. In this work, a scoring based approach is proposed to reward or punish agents for the given task execution.…”
Section: Related Workmentioning
confidence: 99%
“…In Feng et al, 21 a hybrid task algorithm based on score incentive mechanism (TASIM) for complex task execution in WSNs is proposed. Sensor nodes are ranked based on their residual resources and services capacities.…”
Section: Multi-actuator Task Allocationmentioning
confidence: 99%
“…It is observed that the proposed algorithm can extend the network lifetime. In the literature [31], to balance network load, a task allocation algorithm is proposed based on score incentive mechanism (TASIM) for WSNs. In TASIM, the score is proposed to reward or punish sensor nodes' task execution in clusterbased WSNs.…”
Section: Task Collaboration Schemes Of Mwmsnmentioning
confidence: 99%
“…It is observed that the TASIM can balance network load and reduce the network lifetime. Most of the existing task allocation algorithms are based on multi-objective optimization methods, while accounting for the task completion time [31], [32], energy consumption [30], [33], [34], load balancing degree [33], [35], and service reliability [36], [37]. Most of these solutions adopt heuristic methods, which are deterministic and non-retrospective.…”
Section: Task Collaboration Schemes Of Mwmsnmentioning
confidence: 99%